HUBUNGAN KADAR SOLUBLE CD40 LIGAND DENGAN GAGAL JANTUNG AKUT PADA PASIEN INFARK MIOKARD AKUT - , Putrika Prastuti Ratna Gharini, DR. dr. Budi Yuli Setianto, SpPD(K), SpJP(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Soluble CD40 ligand (sCD40L) is released by activated platelets and plays a crucial role in the progression and outcome of acute myocardial infarction (AMI). The study was conducted to determine the differences of sCD40L level in patients with AMI with or without cardiac events particularly of acute heart failure (AHF) Method: This study used cross-sectional method on patients with AMI admitted in ICCU Dr. Sardjito General Hospital. Consecutive sampling was conducted. The diagnosis of AHF based on Killip criteria. Determination of sCD40L level by ELISA method. Statistical methods for assessing differences of the level with Student T-test. Multivariate analysis was performed with stepwise forward logistic regression to assess whether this difference wass independent of other variables. Threshold value was determined by ROC curve. Results: The study involved 59 subjects with a mean age of 56 years. SCD40L levels were higher in AMI patients with AHF (9307 Â± 1995 pg/ml), compared to AMI patients without AHF (7497 Â± 2488 pg/ml, p = 0.005). On multivariate analysis, the variables sCD40L levels (p = 0.048) and creatinine (p = 0.006) were found statistically significantly different. ROC curve analysis of the sCD40L levels provide the highest AUC value was the threshold value of sCD40L 9000 pg/mL. The level of sCD40L â¥ 9000 pg/mL was defined as the threshold value to indicate the increased incidence of AHF. At this threshold value, the odds ratio was of 4.125 with 95% CI 1.3 to 13.1. Conclusion: sCD40L levels were significantly higher in AMI patients with AHF than in those without AHF. The threshold value was 9000pg/mL with the odds ratio 4.125.